Analysis of practices of management environmental and its impacts on productivity of shrimp farming in Ceara State - Ana Maria MaurÃcio AraÃjo (2015)
Shrimp farming has been consolidated as one of the most promising economic activities of the Northeast, where it has also been shown to be responsible for high negative impacts on the coastal environment. The research problem was to see how productivity is affected by the adoption of environmental management practices by analyzing the interaction between the productivity factor and other environmental management factors. To do so, we estimated the linear type regression analysis, to obtain a mathematical equation which quantify the relationship between productivity and other variables. The survey was conducted in 60 shrimp farms located in CearÃ, on farms intended only for fattening phase. Were raised environmental management practices adopted by producers and created management indices,where these indices were aggregated into a single index that along with the variables that describe the productive characteristics and location of the farms originated econometric linlog semi-logarithmic models. Regression analysis showed that the yield is better explained by the storage density, intensive production system periodic servicing. Environmental management is not configured as a factor that influences productivity, justifying the low level of environmental management by shrimp farmers.